The role of native technology in science education in developing countries: A Caribbean perspective - George, June M.
This paper examines the role that socially relevant science and technology curricula can play in the context of a developing country. It discusses the place of technology in socially relevant science curricula, and cultural background and education in technology. The steelpan is used to present an example of this type of lesson
Keywords: Customs and traditions